International Branch Campuses: The New Platonic Academy - He, Lan; Wilkins, Stephen (International Higher Education, 2020)
International branch campuses (IBCs) may be compared to the ancient Platonic Academy. In recent years, IBCs have evolved from their initial role as an instrument and medium for education aid or revenue generation, to becoming hubs of knowledge transfer and knowledge diplomacy. In the future, this new role may bring about win-win outcomes for source countries, host countries, institutions, and knowledge recipients.